2022
DOI: 10.1111/acer.14982
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative examination of the decision‐making process of simultaneous alcohol and cannabis use: Intentions and willingness

Abstract: Background Alcohol and cannabis use are common among young adults and most young adults who use both substances have used them simultaneously (i.e., using both substances so their effects overlap). Because simultaneous use is associated with a greater number and severity of consequences than single substance use, research is needed to examine the decision‐making process of engaging in this high‐risk behavior. We conducted a qualitative examination of intentions (i.e., plans) and willingness (i.e., one's openne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Willingness fully explained the relationship between perceived vulnerability and simultaneous use, such that lower perceived vulnerability of simultaneous use on a given day leads young adults to feel more willing to engage in simultaneous use, which resulted in an increased likelihood to engage in simultaneous use on that day. Our prior qualitative research (Boyle et al, 2023) found that young adults reported that context influences one’s willingness to engage in simultaneous use. Young adults described being more willing to engage in simultaneous use in locations that were familiar and safe (i.e., friend’s house, one’s home).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Willingness fully explained the relationship between perceived vulnerability and simultaneous use, such that lower perceived vulnerability of simultaneous use on a given day leads young adults to feel more willing to engage in simultaneous use, which resulted in an increased likelihood to engage in simultaneous use on that day. Our prior qualitative research (Boyle et al, 2023) found that young adults reported that context influences one’s willingness to engage in simultaneous use. Young adults described being more willing to engage in simultaneous use in locations that were familiar and safe (i.e., friend’s house, one’s home).…”
Section: Discussionmentioning
confidence: 99%
“…Also, our recent qualitative work with young adults who engage in simultaneous use suggests simultaneous use willingness is often based on immediate contextual factors (i.e., location, who they are with, and availability of substances), which are more likely to be known close in time to the substance use event. Also, our qualitative work suggests one’s intentions or plans for simultaneous use can vary from planning weeks in advance to a short time before actual use (Boyle et al, 2023). Thus, intentions and willingness measured in the evening were assumed to be more proximal to behavior and better reflective of intentions and willingness for that day.…”
Section: Discussionmentioning
confidence: 99%
“…Social Cognitive Theory (SCT) [ 39 ] highlights the dynamic interplay of one’s social context (e.g., social roles, social norms) and cognitions such as outcome expectancies (e.g., perceived risks or consequences vs. benefits) in relation to one’s behaviors. For example, an individual’s perceptions of how socially acceptable or normative cannabis use is likely depends on the nature and extent of their exposure to use within their social networks, and these perceptions ultimately impact their personal use [ 9 12 , 37 , 40 42 ]. Additionally, the expected outcomes of use – either positive or negative – influence whether one uses cannabis; if one expects positive outcomes, like a pleasurably psychological experience, they are more likely to use, while if one expects negative outcomes, like health risks or addiction, they may be less likely to use [ 9 12 , 37 , 40 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an individual’s perceptions of how socially acceptable or normative cannabis use is likely depends on the nature and extent of their exposure to use within their social networks, and these perceptions ultimately impact their personal use [ 9 12 , 37 , 40 42 ]. Additionally, the expected outcomes of use – either positive or negative – influence whether one uses cannabis; if one expects positive outcomes, like a pleasurably psychological experience, they are more likely to use, while if one expects negative outcomes, like health risks or addiction, they may be less likely to use [ 9 12 , 37 , 40 42 ]. Moreover, if one perceives negative implications of others (e.g., family members or children in the home) being exposed to cannabis use (e.g., health risks, enticing youth), they may be more likely to implement restrictions about cannabis use in the home or in the presence of children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation